Analysing the Impact of Traffic Incidents on the Travel Time Reliability of Freeway High-Occupancy Vehicle Lanes - Xianzhe Chen; Yajie Zou; Jinjun Tang; Yichuan Peng; Lingtao Wu; Yuming Jiang (Discrete Dynamics in Nature and Society)
This study aims to examine the impact of traffic incidents occurring on general purpose lanes (GPLs) on the travel time reliability of high-occupancy vehicle (HOV) lanes on freeways and to evaluate the differences of travel time reliability on GPLs and HOV lanes under the same incident conditions. In this paper, an empirical travel time reliability analysis is conducted using the travel time and incident data collected between 2009 and 2012 on Interstate 5 and Interstate 405 of the Seattle metropolitan area. Three incident types (i.e., shoulder incident, single lane incident, and multiple lane incident) are considered. Two measures, percentile-based indicator and inflow–percentile travel time function, are used. The results suggest that incidents result in lower values of travel time reliability for all the measures. The results also show that multiple lane incident type has the most significant impact on the freeway route travel time reliability, while shoulder incident type has the least impact. Generally, HOV lanes have higher travel time reliability than GPLs under the same incident types. The findings in this study provide useful decision support for transportation agencies to improve travel time reliability on freeways.